Oral health assessment protocol in primary care - Moimaz, Suzely Adas Saliba; Melo, Lúcia Maria Lima Lemos De; Garbin, Cléa Adas Saliba; Garbin, Artênio José Ísper; Saliba, Nemre Adas (Faculdade São Leopoldo Mandic, 2015)
Objective:The aim of this study was to analyze the oral health service performance in a certain municipality and also to develop a diagnostic evaluation protocol of Oral Health in Primary Care.Methods:This is a descriptive, quantitative and qualitative research. The research site chosen was in the city of Pereira Barreto, State of São Paulo Brazil, since it makes use of the Family Health Strategy as the structuring care model of the Health Care System in 100% of the population as well as oral health teams implemented and oral health secondary care. Data were obtained through interviews with the manager, six dentists, six oral health assistants and six community health workers. Document analysis of the Municipal Health Plan was also conducted along with the Dental Health Agenda and on-site observation of the dental structure.Results:The city Health Plan presents a detailed description of the municipality general situation, the oral health agenda recommends, in its implementation phase, the three main areas as a core in Family Health Strategy as follows: health unit, family and community.The survey found that the main form of access of the population to services was the spontaneous demand and there were only two Family Health teams without focus on oral health.Conclusion:The analysis of the service performed; made possible to develop a protocol with specific Oral Health dimensions to support the manager in defining intervention strategies

Objetivo:Analisar o funcionamento do serviço de Saúde Bucal em um município e desenvolver um protocolo de avaliação diagnóstica da Saúde Bucal na Atenção Básica.Métodos:Trata-se de uma pesquisa quanti-qualitativa, descritiva. O local da pesquisa foi Pereira Barreto, São Paulo, por apresentar a Estratégia Saúde da Família como modelo assistencial estruturante do Sistema de Atenção à Saúde em 100% da população; equipes de saúde bucal implantadas; atenção secundária em saúde bucal. Os dados foram obtidos por meio de entrevistas com o gestor, 6 cirurgiões-dentistas, 6 auxiliares de saúde bucal e 6 agentes comunitários de saúde. Foram realizadas também análise documental do Plano Municipal de Saúde, Agenda de Saúde Bucal e observação in loco da estrutura odontológica.Resultados:O município oferta serviços de saúde bucal com integração entre atenção básica e especializada, sendo a atenção básica ordenadora da rede. O Plano Municipal de Saúde apresenta descrição detalhada da situação geral do município; a agenda de saúde bucal preconizada em fase de implantação contempla os três eixos de atuação da Estratégia Saúde da Família: unidade de saúde, família e comunidade. O inquérito identificou que a principal forma de acesso da população aos serviços era a demanda espontânea; havia duas equipes de Saúde da Família sem equipes de Saúde bucal.Conclusão:A análise do funcionamento do serviço possibilitou desenvolver um protocolo com dimensões específicas de Saúde Bucal para subsidiar o gestor na definição de estratégias de intervenção.
Protocolo de Avaliação da Saúde Bucal na Atenção Básica
Keywords: Health evaluation; Health management; Oral health; Primary health care; Saúde bucal; Atenção primária à saúde; Avaliação em saúde; Gestão em saúde